The role of gut archaea in the pig gut microbiome: a mini-review - Yang, Jianbo; Chen, Routing; Peng, Yunjuan; Chai, Jianmin; Li, Ying; Deng, Feilong (Frontiers in Microbiology, 2023)
The gastrointestinal microbiota of swine harbors an essential but often overlooked component: the gut archaea. These enigmatic microorganisms play pivotal roles in swine growth, health, and yield quality. Recent insights indicate that the diversity of gut archaea is influenced by various factors including breed, age, and diet. Such factors orchestrate the metabolic interactions within the porcine gastrointestinal environment. Through symbiotic relationships with bacteria, these archaea modulate the host's energy metabolism and digestive processes. Contemporary research elucidates a strong association between the abundance of these archaea and economically significant traits in swine, such as growth rate and meat quality. This review elucidates the multifaceted roles of gut archaea in swine and underscores the imperative for strategic interventions to modulate their population and functionality. By exploring the probiotic potential of gut archaea, we envisage novel avenues to enhance swine growth, health, and product excellence. By spotlighting this crucial, yet underinvestigated, facet of the swine gut microbiome, we aim to galvanize further scientific exploration into harnessing their myriad benefits.